Contemporary issues in end user computing - Mahmood, Mo Adam. (Advances in end user computing,, 2007)
This book includes empirical and theoretical research concerned with all aspects of end user computing including development, utilization, and management and covering Web-based end user computing tools and technologies, end user computing software and trends, and end user characteristics and learning.